Proposta de intervenção terapêutica à criança recém-hospitalizada à luz da teoria psicanalítica winnicottiana: privacidade e espaço pessoal - Rocha, Ana Cristina D´Oliveira (2007)
The objective of this paper is to propose and analyze a therapeutic intervention of a psycho-analytical character by playing with a recently hospitalized child in the light of the Winnicottian theory. The specific objective is to analyze the contributions from the Environmental Psychology to the proposal of therapeutic intervention, specifically the privacy and personal space phenomena. A study with two subjects was conducted in a public hospital, with a 5-year-and-6- month boy and a 4-year-and-11-month girl. The methodology consisted in: semi-guided interview with the respective mothers and therapeutic intervention by playing with each child in the first two days of hospitalization. With the collected data it was possible to make a psychological diagnostic hypothesis for each case, utilizing the Winnicottian theory. The hypothesis determined in which developmental stage the child supposedly was and how he or she has seemed to relate to reality since they were babies, developing individual manners of playing. The manner in which each child has developed seemed consistent with the reactions and the rapport established in playing in intervention with the researcher. The privacy and personal space phenomena were observed during the intervention process and were also coherent with the ways each child developed since babies to the reality, expression of their feelings, emotions and perceptions at the moment of intervention. It seemed to have been fundamental to the establishment of interaction and its continuity, as well as the continuity of the established playing, the knowledge of and respect for each child s need and desire for privacy and their own ways to mark the personal space. It was also realized that offering the possibility of playing, that was made in a noninvading way and coherent with each child s desires and needs, contributed for the building of an environment where there was acceptance and, therefore, they were able to express themselves according to their real self. It was concluded that there is need for more studies to be developed about how to offer hospitalized children a caring environment in which playing is incentivated, in the beginning of hospitalization. The identification and the expressions of privacy and personal space by the subjects could contribute to the